Antibacterial Activity of Foot Spray Preparations Extract of Jeruk Purut Leaves (Citrus Hystrix) and Robusta Coffee Leaves (Coffea canephora) Against Staphylococcus epidermidis - Lestari, Seri; Nasution, Muhammad Amin; Dalimunthe, Gabena indrayani; Lubis, Minda Sari (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2024)
A problem that is often found in Indonesia, especially on the feet and causes many people to lack self-confidence, is smelly feet. This odor is caused by bacteria on the skin and inside shoes. Bacteria like Staphylococcus epidermidis produce an unpleasant smell by degrading leucine from sweat, leading to the formation of isovaleric acid, which emits a foul odor. This issue can be addressed using plant materials such as jeruk purut leaves (Citrus hystrix) and robusta coffee leaves (Coffea canephora). This research uses an experimental method. Jeruk purut leaves and robusta coffee leaves are extracted through maceration and then formulated into a foot spray with extract concentrations of 1.5%, 2%, and 2.5%. The evaluation results indicate that the foot spray formulation meets the stability test parameters, including organoleptic properties and pH. In terms of hedonic testing, panelists preferred Formula 1, and no formula caused skin irritation. Antibacterial testing of all formulations showed strong antibacterial activity, with inhibition zone diameters of 11.9 mm for Formula 1 (1.5% concentration), 12.4 mm for Formula 2 (2% concentration), and 12.8 mm for Formula 3 (2.5% concentration) against Staphylococcus epidermidis. Statistical analysis using One-Way ANOVA showed that the antibacterial activity of the foot spray in inhibiting bacterial growth was significant at a 0.005 level, with a probability value (significance) of 0.00 < 0.05, indicating that the antibacterial activity of the foot spray can affect the growth of Staphylococcus epidermidis.